2021
DOI: 10.1136/bcr-2020-239781
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of unexplained coma and hypokinetic-rigid syndrome in a patient with COVID-19

Abstract: The COVID-19 pandemic has dealt a devastating blow to healthcare systems globally. Approximately 3.2% of patients infected with COVID-19 require invasive ventilation during the course of the illness. Within this population, 25% of patients are affected with neurological manifestations. Among those who are affected by severe neurological manifestations, some may have acute cerebrovascular complications (5%), impaired consciousness (15%) or exhibit skeletal muscle hypokinesis (20%). The cause of the severe cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Analyzing the diagnostic findings and the response to dopaminergic treatment in the three subgroups, it can be assumed that the third (structural and functional basal ganglia damage) represents an example of secondary parkinsonism. In this context, COVID-19 infection has indirectly led to structural alterations in the basal ganglia responsible for different signs and symptoms, including parkinsonism [ 16 , 18 , 23 ]. On the contrary, the second scenario (unmasking of underlying still non-symptomatic PD) might be more intriguing and more interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the diagnostic findings and the response to dopaminergic treatment in the three subgroups, it can be assumed that the third (structural and functional basal ganglia damage) represents an example of secondary parkinsonism. In this context, COVID-19 infection has indirectly led to structural alterations in the basal ganglia responsible for different signs and symptoms, including parkinsonism [ 16 , 18 , 23 ]. On the contrary, the second scenario (unmasking of underlying still non-symptomatic PD) might be more intriguing and more interesting.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 papers were included, describing 20 cases that met our criteria (Table 2). [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In 13 patients, SARS-CoV-2 infection was confirmed with a nasopharyngeal swab, found positive for SARS-CoV-2 in a real time reverse-transcription polymerase chain reaction (RT-PCR) assay. For the residual seven cases reported to have been diagnosed with 8,10,11,15,16,20) the diagnostic means of confirmation were not provided.…”
Section: Resultsmentioning
confidence: 99%
“…The comprehensive literature search yielded a total of 2555 studies from the databases. Overall, 10 studies were eligible according to our inclusion criteria [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. The characteristics of these 10 included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Three out of 10 studies were identified as good quality, while seven were of fair quality, as shown in Table S2 . Studies were primarily downgraded for unclear patient's demographic description [ 27 ], incomplete patient's history presentation [ 24 , 25 , [27] , [28] , [29] , [30] , [31] , [32] ], inadequate diagnostic test results description [ 28 , 30 ], unclear treatment description [ 25 , 27 , 28 , 32 ], incomplete post-intervention condition description [ [23] , [24] , [25] , 29 ], no proper adverse events identification [ [23] , [24] , [25] , [26] , [27] , [28] , [30] , [31] , [32] ] and not enough takeaway lessons [ 23 ]. The most common cause for downgrading studies was no proper adverse events (harms) or unanticipated events being identified and described, which raised concerns if the treatment/intervention/drugs used has more benefit than risks and the if the benefits outweigh the risks.…”
Section: Resultsmentioning
confidence: 99%